Immunohistochemical expression of calmodulin in cutaneous lichen planus: A case-control study - Zeinab Abd El-Samad Ibrahim; Amal Ahmad El-Ashmawy; Yomna Mazid El-Hamd Neinaa; Dareen Abd El-Aziz Mohammad (Wolters Kluwer Medknow Publications, 2019)
Background: Calmodulin (CaM) is a multifunctional intermediate messenger protein that plays important role in cell motility, proliferation, and apoptosis. Therefore, it is thought to be involved in various ways in the apoptotic processes which are implicated in the pathogenesis of lichen planus. Objective: The aim of this study was to evaluate the immunohistochemical expression of CaM in lichen planus lesions in comparison to normal control skin to throw light on its possible role in disease pathogenesis. Patients and Methods: This case-control study was conducted on 50 patients with lichen planus, in addition to 20 age- and sex-matched healthy individuals. Skin biopsy specimens were taken from lesional skin of lichen planus patients as well as normal skin of controls. All were examined for immunohistochemical expression of CaM antibody. Results: There was statistically significant increase of the immunohistochemical expression of CaM in lesional skin of lichen planus patients compared with normal skin of controls (Chi-square test, P < 0.001). No significant correlation could be detected between CaM expression in lesional skin and the studied clinical parameters of lichen planus patients. Limitations: Tha main limitation of this study is its small sample size. Conclusion: CaM is upregulated in cutaneous lichen planus lesions suggesting a possible role in disease pathogenesis. Targeting CaM is expected to be a novel strategy for treatment of lichen planus.